Prototipe Konseling Budaya Berdasarkan Nilai-Nilai Ruwatan untuk Meningkatkan Kesejahteraan Masyarakat Pasca-Bencana Banjir - Ashari Mahfud; Anisatul Latifah; Indah Lestari; Muslikah Muslikah; Cecily Bishops (Pamomong: Journal of Islamic Educational Counseling, 2025)
Flood disasters inflict not only physical and economic damages but also profoundly affect community well-being, particularly in the psychological, social, and spiritual domains of students. A culturally grounded approach holds strategic promise for facilitating post-disaster recovery in Indonesia. This study aims to investigate the values embedded within the ruwatan tradition as a conceptual basis for developing a culturally relevant and adaptive counseling prototype designed to enhance the well-being of students impacted by floods in Central Java, Indonesia. Employing an exploratory qualitative methodology, the research engaged 20 purposively selected participants as data sources. Data collection involved in-depth interviews, participatory observations, and document analysis of ruwatan practices within local communities. Thematic data analysis was performed through an interpretative lens using Nvivo software. Findings reveal that ruwatan values—comprising inner purification, social reconciliation, and transformation—can be synthesized into a three-stage cultural counseling prototype: contextual assessment, symbolic-narrative intervention, and reflective exploration of post-disaster life meaning. These outcomes suggest the importance for school counselors to integrate local wisdom values when fostering psychological well-being in disaster-affected populations.